On L (1)-weak ergodicity of nonhomogeneous discrete Markov processes and its applications - Mukhamedov, Farrukh (Springer, 2013)
In the present paper we investigate the L1-weak ergodicity of nonhomogeneous discrete Markov processes with general state spaces. Note that the L1-weak ergodicity is weaker than well-known weak ergodicity.We provide a necessary and sufficient condition for such processes to satisfy the L1-weak ergodicity. Moreover, we apply the obtained results to establish L1-weak ergodicity of discrete time quadratic stochastic processes. As an application of the main result, certain concrete examples are also provided.